2003
DOI: 10.1046/j.1432-1033.2003.03713.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different isoforms of eEF1A in the nuclear fraction of human T‐lymphoblastic cancer cell line specifically binding to aptameric cytotoxic GT oligomers

Abstract: GT oligomers, showing a dose-dependent cytotoxic effect on a variety of human cancer cell lines, but not on normal human lymphocytes, recognize and form complexes with nuclear proteins. By working with human T-lymphoblastic CCRF-CEM cells and by using MS and SouthWestern blotting, we identified eukaryotic elongation factor 1 alpha (eEF1A) as the main nuclear protein that specifically recognizes these oligonucleotides. Western blotting and supershift assays confirmed the nature of this protein and its involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 47 publications
3
54
0
Order By: Relevance
“…4). The increased level of eEF1A in cancers has been described previously (20,21), and the results shown here suggest that a common cellular response to protein Figure 5. Composite data.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…4). The increased level of eEF1A in cancers has been described previously (20,21), and the results shown here suggest that a common cellular response to protein Figure 5. Composite data.…”
Section: Resultssupporting
confidence: 82%
“…Immunoblotting studies revealed dramatic increase in eEF1A levels, suggesting that defects in protein synthesis quality control are associated with breast cancer. Because eEF1A expression is also increased in other cancers (20,21), it is likely that this result reflects a more general response to aberrant growth (22), unlike the specific expression of certain Ubconjugating enzymes in breast cancer. Significantly, none of our findings were reproduced in a well-defined cell culture system that is used as a model system for breast cancer (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…61 Another eEF1A isoform has also been identified as the main nuclear protein in human T-lymphoblastic CCRF-CEM cells that specifically recognizes GT oligomers to form a cytotoxicity-related complex that shows a dose-dependent cytotoxic effect on a variety of human cancer cell lines but not on normal human lymphocytes. 62 This ability of both eEF1A1 and eEF1A2 to form complexes with so many different proteins, which might be explained by the partially unstructured conformation that has been detected in solution for eEF1A, 30 reveals a more complex role for these eEF1 subunits beyond protein biosynthesis. In fact, the multicomponent eEF1 system appears to behave as a sophisticated regulatory factor rather than as a mere "housekeeping" element of the cell, and its activity appears to be coordinated with cell replication.…”
Section: Discussionmentioning
confidence: 99%
“…An isoform of eEF1A1 with a more basic isoelectric point was identified in human haematopoietic cancer cell lines but not in normal lymphocytes raising the possibility that posttranslation modifications of eEF1A1 could be involved in cancer development and progression of haematopoietic tumours (Dapas et al, 2003). The selective inhibition of eEF1A1 isoform by specific GT aptameric oligonucleotides, carried by the ethoxylated polyethylenimine, a weak basic polycation, has been demonstrated to exert specific cytotoxic effect and dose-dependent cell growth inhibition on lymphoblastic cancer cells (Scaggiante et al, 2005).…”
Section: Notementioning
confidence: 99%